Ethnic Media in the Digital Age
1 online resource (216 pages)
Keywords: Ethnic media are media produced for, and frequently by, immigrants, ethnic and linguistic minority groups, and indigenous populations. These media represent a sector of the broader media industry that has seen considerable growth globally, even while many mainstream, legacy media have struggled to survive or have ceased to exist, largely due to the emergence of new communication technologies. What is missing in the literature is a careful examination of ethnic media in the digital age. The original research, including case studies, in this book provides insight into (1) what new trends are emerging in ethnic media production and consumption; (2) how ethnic media are adapting to changing technologies in the media landscape of our times; and (3) what enduring roles ethnic media perform in local communities and in an increasingly globalized world. The ethnic media that contributors discuss in this book are produced for and distributed across a variety of platforms, ranging from broadcasting and print to online platforms. Additionally, these media serve numerous immigrant, ethnic, and indigenous communities who live in and trace their origins back to a variety of regions of the world, including Africa, Asia, Europe, North America, and Oceania.